Manajemen Konflik: Tinjauan Pustaka - Saqif Haidarravy; Muhammad Isa Anshori (Universitas 17 Agustus 1945 Semarang, 2023)
Conflict management studies are needed because it is still difficult to find previous studies that address this topic in depth and considering that some companies have not optimally implemented conflict management programs both inside and outside the company. The purpose of this literature review is to find and examine various definitions of conflict management based on the broad context of previous research. The type of data used in this literature review is a type of secondary data in the form of articles and research journals totaling 29 articles and research journals both nationally and internationally with the journal publication year 2011-2022. The data collection method used in this literature review was a literature review with the help of the Google Scholar and Mendeley databases. The data analysis technique used in this literature review is a bibliometric-based data analysis technique with the help of VosViewer 1.6.19 software to obtain a more comprehensive visualization of conflict management. The results of this literature review are based on the results of bibliometric data analysis through the context of previous research which shows that each study places a different focus or concentration on conflict management. Teams and organizations have 29 outcomes from conflict management in the form of leadership style, job satisfaction, innovation and productivity are the four antecedents of conflict management. Conflict Management Style, Job Satisfaction, Organizational Performance, Innovation, Leadership Style, Emotional Intelligence are the six consequences.